A pilot study on the effect of cognitive training on BDNF serum levels in individuals with Parkinson’s disease - Angelucci, Francesco; Peppe, Antonella; Carlesimo, Giovanni A.; Serafini, Francesca; Zabberoni, Silvia; Barban, Francesco; Shofany, Jacob; Caltagirone, Carlo; Costa, Alberto (Frontiers in Human Neuroscience, 2015)
Parkinson’s disease (PD) patients, besides motor dysfunctions, may also display mild cognitive deficits (MCI) which increase with disease progression. The neurotrophin brain-derived neurotrophic factor (BDNF) plays a role in the survival of dopaminergic neurons and in the regulation of synaptic connectivity. Moreover, the brain and peripheral level of this protein may be significantly reduced in PD patients. These data suggest that a cognitive rehabilitation protocol aimed at restoring cognitive deficits in PD patients may also involve changes in this neurotrophin. Thus, in this pilot study we evaluated the effect of a cognitive rehabilitation protocol focused on the training of executive functioning and measured BDNF serum levels in a group of PD patients with mild cognitive impairment, as compared to the effect of a placebo treatment (n=7/8 group). The results showed that PD patients undergoing the cognitive rehabilitation, besides improving their cognitive performance as measured with the Zoo Map test, also displayed increased serum BDNF levels as compared to the placebo group. These findings suggest that BDNF serum levels may represent a biomarker of the effects of cognitive rehabilitation in PD patients affected by MCI. However, the functional significance of this increase in PD as well as other neuropathological conditions remains to be determined.